Implementation Compress Warm To Patients Dengue Hemorrhagic Fever With Problems Nursing Hyperthermia In The Kemuning Room Of Dustira Class II Hospital - Hikmat Rudyana; Syintang Rasi Maliki; Gunawan Irianto; Dedi Supriadi (Jurnal EduHealth, 2024)
DHF cases in Indonesia continue to increase, in 2021 there were 73,518 cases with a death rate of 705 people. In 2022, there were 131,265 cases with 1,183 deaths. In the period January - July 2023, 42,690 people were infected with DHF and 317 people died. One of the symptoms of Dengue Haemorrhagic Fever (DHF) is a sudden high fever (more than 38.0 C) that lasts continuously for 2 to 7 days. Fever if not handled properly can cause other effects, if the temperature is above 38 then it can increase sweating, pale, clammy, and cold skin, general weakness, tachycardia with a weak pulse, nausea or vomiting, dizziness, mild headache, or fainting. Temperatures above 40 degrees can cause hot, red, dry skin, tachycardia with a strong pulse, delirium, seizures, or coma. The purpose of this study was to analyze and describe the application of warm compresses in overcoming hyperthermia problems in Dengue Haemorragic Fever patients. The method used in the preparation of this scientific work is descriptive with a Case report approach to nursing care by applying Evidence based practice nursing Warm compresses on 1 patient with a body temperature of 38.0ºC. Data collection methods used in this case study are interviews, observation and physical examination. The results of the case study obtained the application of warm compresses was able to reduce body temperature in Dengue Haemorrhagic Fever patients with hyperthermia nursing problems. It is recommended that nurses can combine pharmacological therapy with nonpharmacology, namely warm compresses to help reduce body temperature in patients.